Clinical risk predictors for bradycardia, supraventricular tachycardia and epilepsy necessitating therapy in patients with unexplained syncope monitored by insertable cardiac monitor. (25th November 2020) - Onuki, T; Shoji, M; Kikuchi, M; Asano, T; Suzuki, H; Tannno, K; Shinke, T
Abstract: Background: Insertable cardiac monitors (ICMs) allow for lengthy monitoring of cardiac rhythm and improve diagnostic yield in patients with unexplained syncope. In most cardiac syncope cases, sick sinus syndrome, atrioventricular block, and paroxysmal supraventricular tachycardia (SVT) are detected using ICMs. On the other hand, epileptic seizures are sometimes diagnosed as unexplained syncope because in these situations, the loss of consciousness is a similar manifestation. Thus, the population of patients with unexplained syncope monitored by ICMs includes epileptic patients. Clinical risk factors for bradycardia, SVT and epilepsy that necessitate therapy in patients with unexplained syncope are not well known. If these risks can be clarified, clinicians could provide more specific targeted monitoring. Purpose: We aimed to identify these predictors. Methods: We retrospectively reviewed medical records of consecutive patients who received ICMs to monitor unexplained syncope in three medical facilities. We performed Cox's stepwise logistic regression analysis to identify significant independent risk factors for bradycardia, SVT, and epilepsy. Results: One hundred thirty-two patients received ICMs to monitor unexplained syncope. During the 17-month follow-up period, 19 patients (10 patients had sick sinus syndrome and 9 had atrioventricular block) needed pacemaker for bradycardia; 8 patients (3 had atrial flutter, 4 had atrial tachycardia, and 1 had paroxysmal atrial fibrillation) needed catheter ablation for SVT; and 9 patients needed antiepileptic agents from the neurologist.Stepwise logistic regression analysis indicated that syncope during effort (odds ratio [OR] = 3.41; 95% confidence interval [CI], 1.21 to 9.6; p=0.02) was an independent risk factor for bradycardia. Palpitation before syncope (OR = 9.46; 95% CI, 1.78 to 50.10; p=0.008) and history of atrial fibrillation (OR = 10.1; 95% CI, 1.96 to 52.45; p=0.006) were identified as significant independent prognostic factors for SVT. Syncope while supine (OR = 11.7; 95% CI, 1.72 to 79.7; p=0.01) or driving (OR = 15.6; 95% CI, 2.10 to 115.3; p=0.007) was an independent factor for epileptic seizure. Conclusions: ICMs are useful devices for diagnosing unexplained syncope. Palpitation, atrial fibrillation and syncope during effort were independent risk factors for bradycardia and for SVT. Syncope while supine or driving was an independent risk factor for epilepsy. We should carefully follow up of patients with these risk factors. Funding Acknowledgement: Type of funding source: None